## 1. 5x-4=3x-2 - Symbolab

Frequently Asked Questions (FAQ) · What is the answer to 5x-4=3x-2 ? The answer to 5x-4=3x-2 is x=1 · Solve for x: 5x-4=3x-2. The solution is x=1.

Detailed step by step solution for 5x-4=3x-2

## 2. Graph f(x)=5x^4+3x^2 - Mathway

f(x)=5x4+3x2 f ( x ) = 5 x 4 + 3 x 2. Step 1. Graph. f(x)=5x4+3x2 f ( x ) = 5 x 4 + 3 x 2. Step 2. image of graph. f(x)=5x4+3x2 f ( x ) = 5 x 4 + 3 x 2 ...

Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with step-by-step explanations, just like a math tutor.

## 3. Solve 5x^4-3x^2-2=0 | Microsoft Math Solver

2x4-3x2-5=0 Four solutions were found : x= 0.0000 - 1.0000 i x= 0.0000 + 1.0000 i x = ±√ 2.500 = ± 1.58114 Step by step solution : Step 1 :Equation at the end ...

Solve your math problems using our free math solver with step-by-step solutions. Our math solver supports basic math, pre-algebra, algebra, trigonometry, calculus and more.

## 4. Solve : 5x-4=3x-2 | Byjus Mathsolver

To solve a linear equation in one variable using transposition method. Now we need to transpose the variable term present in the RHS to LHS.

Math Solver

## 5. How do you solve the inequality 5x+4<=3x^2 and write your answer ...

11 dec 2017 · The solution is x∈(−∞,−0.59]∪[2.26,+∞). Explanation: Let's rewrite the inequality. 5x+4≤3x2. 3x2−5x−4≥0. Let f(x)=3x2−5x−4.

The solution is x in (-oo, -0.59] uu[2.26, +oo) Let's rewrite the inequality 5x+4<=3x^2 3x^2-5x-4>=0 Let f(x)=3x^2-5x-4 The roots of the quadratic equation 3x^2-5x-4=0, are x = ( 5+-sqrt ((-5)^2-(4)* (3) * (-4)) ) /(6)=(5+-sqrt(73))/(6) x_1=(5-sqrt73)/6=-0.59 x_2=(5+sqrt73)/6=2.26 Let's build the sign chart color(white)(aaaa)xcolor(white)(aaaaa)-oocolor(white)(aaaaaaa)x_1color(white)(aaaaaa)x_2color(white)(aaaa)+oo color(white)(aaaa)x-x_1color(white)(aaaaa)-color(white)(aaaa)0color(white)(aaa)+color(white)(aaaa)+ color(white)(aaaa)x-x_2color(white)(aaaaa)-color(white)(aaaa)#color(white)(aaaa)#-color(white)(aa)0color(white)(aa)+ color(white)(aaaa)f(x)color(white)(aaaaaaa)+color(white)(aaaa)0color(white)(aaa)-color(white)(aa)0color(white)(aa)+ Therefore, f(x)>=0 when x in (-oo, x_1] uu[x_2, +oo) graph{3x^2-5x-4 [-11.39, 11.11, -6.615, 4.635]}

## 6. Solve for x 3(5x-4)=4(3x-2) | Mathway

Move all terms containing x x to the left side of the equation.

Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with step-by-step explanations, just like a math tutor.

## 7. Solve (3x-2)(5x+4) - Microsoft Math Solver

3x-2=x+4 One solution was found : x = 3 Rearrange: Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation ...

Solve your math problems using our free math solver with step-by-step solutions. Our math solver supports basic math, pre-algebra, algebra, trigonometry, calculus and more.

## 8. Solve Linear inequalities 5x-4<=3x-2 Tiger Algebra Solver

Rearrange: Rearrange the equation by subtracting what is to the right of the less equal sign from both sides of the inequality : 5*x-4-(3*x-2)≤0 ...

See AlsoFx Channel On OptimumAlgebra 5x-4<=3x-2 Solver Shows Steps Quadratic Equations, Exponents, Polynomials ...

## 9. Solve inequalities with Step-by-Step Math Problem Solver - QuickMath

4x- 2-3x = 4 + 6. by combining like terms and then by adding 2 to each member ... Example 1 Solve 5x - 7 = 2x - 4x + 14. Solution First, we combine like ...

Solve linear or quadratic inequalities with our free step-by-step algebra calculator

## 10. Solve the following equation (3x - 2)(5x - 4) = (3x - 2)2 - Myschool.ng

Solve the following equation (3x - 2)(5x - 4) = (3x - 2)2.

Solve the following equation (3x - 2)(5x - 4) = (3x - 2)2

## 11. Solve Simplification or other simple results 5x^4 - Tiger Algebra

Equations : Tiger Algebra gives you not only the answers, but also the complete step by step method for solving your equations 5x^4*-3x^2 so that you ...

Equations : Tiger Algebra gives you not only the answers, but also the complete step by step method for solving your equations 5x^4*-3x^2 so that you understand better

## 12. How do you differentiate f(x)=5x^4-3x^2+2? - Socratic

12 apr 2015 · Use three properties of derivatives: The derivative of a sum (or difference) is the sum (or difference) of the derivatives.

Use three properties of derivatives: The derivative of a sum (or difference) is the sum (or difference) of the derivatives. This tells us that we can find the derivatives of each term seperately and add(subtract) the derivatives. The derivative of a constant time a function is the constant times the derivative. This tells us that the coefficients will simply multiply the derivatives of the variable factors. The power rule tells us the the derivative of x^n is nx^(n-1). (You con include the derivative of a constant is 0.) So: f(x) = 5x^4-3x^2+2. f'(x) = 5(4x^3) - 3(2x^1) + 2(0). So, f'(x) = 20x^3 - 6x.

## 13. Find the quotient. (5x4 - 3x2 + 4) ÷ (x + 1) - Cuemath

Find the quotient. (5x4 - 3x2 + 4) ÷ (x + 1) The quotient when (5x4 - 3x2 + 4) ÷ (x + 1) is 5x3 - 5x2 + 2x - 2.

Find the quotient. (5x4 - 3x2 + 4) ÷ (x + 1) The quotient when (5x4 - 3x2 + 4) ÷ (x + 1) is 5x3 - 5x2 + 2x - 2.

## 14. Solve linear and quadratic equations with Step-by-Step Math ... - QuickMath

Example 1 5 x 4 = 20 is an identity. Example 2 2 + 3 = 5 is an identity. Example 3 2x + 3x = 5x is an identity since any value substituted for x will ...

Solve quadratic equations, radical, exponential and rataional equations with our free step-by-step math equation solver